The Making of Speculative Biodiesel Commodities on the Agroenergy Frontier of the Brazilian Northeast. Issue 6 (28th August 2020) - Manzi, Maya
Abstract: In this paper, I examine the speculative dimensions of biodiesel production in Northeast Brazil under the National Program for the Production and Use of Biodiesel (PNPB), by focusing on the case of castor oil plant ( Ricinus communis ) in semi‐arid Bahia, a promising flex crop that was said to generate social, environmental and economic benefits, especially for the historically marginalised Northeast peasantry. I argue that speculative practices over castor have relied on state policies and discourses as well as biophysical and biotechnological (im)materialities that are transforming agrarian relations in ways that compromise peasants' control over their (re)productive systems while promoting the expansion of the agroindustrial frontier. By examining the everyday, performative and place‐based character of speculative biodiesel practices and their uneven and contested socioenvironmental implications, this paper contributes to current political ecology debates on the nexus between agroenergy development, nature's capitalist valuation and rural dispossession. Resumo: Neste artigo, examino as dimensões especulativas da produção de biodiesel no Nordeste do Brasil, no âmbito do Programa Nacional de Produção e Uso do Biodiesel (PNPB), concentrando‐me no caso da mamona ( Ricinus communis ) no semiárido baiano, uma cultura dita flexível que prometia gerar benefícios sociais, ambientais e econômicos, especialmente para os camponeses do Nordeste historicamente marginalizados. Argumento que práticas especulativas sobre a mamona se constituíram através de políticas e discursos do Estado, bem como de (im)materialidades biofísicas e biotecnológicas que transformaram as relações agrárias, comprometendo o controle dos camponeses sobre seus sistemas (re)produtivos e promovendo a expansão da fronteira agroindustrial. Ao examinar o caráter cotidiano, performativo e situado das práticas especulativas de biodiesel, bem como suas implicações socioambientais desiguais e contestadas, este artigo contribui para os debates atuais em ecologia política sobre o nexo entre desenvolvimento agroenergético, valorização capitalista da natureza e despossessão rural.